Unfolding the form from within: East and Southeast urban Asia, its postcolonial condition, and its ephemeral architectural "displayness". Issue 2 (4th March 2023) - Lin, Francis Chia Hui
ABSTRACT: This paper attempts to coin a term "displayness" to emphasis the internal form of spatiotemporal display. In contemporary Asia, its displayness is argued to be the critical dynamics. Noticeably, this displayness implies a postcolonial perspective to question contemporary Asia's complicated built heteroglossia. In other words, due to the inescapable marriage between the external cultural politics and the local essence, the Asian built environment showcases not only a binary identification of these two forces but also an emergent new identity in between, which, arguably, is identifiable of being urban Asian. The commercial exhibitions temporarily built along or within major shopping centres are the examples. This paper intends to face and analyse these temporary and seemingly superficial built objects as representations of the registered historicity of contemporary Asia. This paper analyses selected cases of temporary commercial exhibitions in Singapore and Taiwan which reflect the economic-political intervention into the Asian built environment, both as architectural landmarks and from the collective sense of urbanism. As a methodology, the architectural manifestations delivered as a form of understanding are analysed from the assistance of these temporal exhibitions' ephemeral character, and this form is argued as a display of contemporary Asia's postcoloniality reflected through its built historicity.